2007
DOI: 10.1002/pbc.21064
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose chemotherapy and autologous stem cell rescue in children with newly diagnosed high‐risk or relapsed medulloblastoma or supratentorial primitive neuroectodermal tumor

Abstract: High-dose chemotherapy may improve the survival of children with newly diagnosed high-risk MB/sPNET, and, to some extent, the survival of those with relapsed MB/sPNET. Further study is necessary to elucidate the efficacy of tandem double HDCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 28 publications
1
56
2
Order By: Relevance
“…26 High-dose chemotherapy with stem cell support may also be beneficial in PNET and medulloblastoma patients, albeit at the cost of significant acute toxicity. [27][28][29][30] Conventional multiagent chemotherapy was able to cure children with earlystage, completely resected newly diagnosed medulloblastoma, but was insufficient for treatment of metastatic or incompletely resected tumors. 31 Many patients in our study had adverse prognostic factors.…”
Section: Supratentorial and Disseminated Pnets Medulloblastomasmentioning
confidence: 99%
“…26 High-dose chemotherapy with stem cell support may also be beneficial in PNET and medulloblastoma patients, albeit at the cost of significant acute toxicity. [27][28][29][30] Conventional multiagent chemotherapy was able to cure children with earlystage, completely resected newly diagnosed medulloblastoma, but was insufficient for treatment of metastatic or incompletely resected tumors. 31 Many patients in our study had adverse prognostic factors.…”
Section: Supratentorial and Disseminated Pnets Medulloblastomasmentioning
confidence: 99%
“…Recently, investigators have examined the efficacy of double or tripletandem HDCT/ASCR for further improvements in the outcome of patients with high-risk solid tumors. Sung et al 8,9 reported improved long-term survival using tandem HDCT/ASCR in patients with advanced neuroblastoma and high-risk brain tumors. Kletzel et al 10 also reported improved survival in a single-arm trial of triple-tandem HDCT/ASCR in patients with high-risk neuroblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] This treatment strategy is based on the hypothesis that a dose escalation might improve the survival of children with high-risk solid tumors. Recently, investigators have examined the efficacy of double or tripletandem HDCT/ASCR for further improvements in the outcome of patients with high-risk solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Additionally, several recent studies have suggested that dose-escalation using tandem HDCT/auto-SCT might further improve outcomes in the treatment of recurrent or high-risk brain tumors. 14,15 In the present study, we prospectively evaluated the feasibility and effectiveness of tandem HDCT/auto-SCT in children o3 years of age with malignant brain tumors. RT was either not given or deferred until 3 years of age if the patient achieved CR after tandem HDCT/auto-SCT.…”
Section: Introductionmentioning
confidence: 99%